A geological/geomorphological and soil transect study of the Chirripo massit and adjacent areas, Cordillera de Talamanca, Costa Rica - Uffelen, J.G. van (1993)
Fig. Tab. Mapas. Sum. (En). También como: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 107